POTENSI ANTIDIABETES DAUN Smallanthus sonchifolius : A SYSTEMATIC LITERATURE REVIEW TERHADAP MEKANISME MOLEKULER DAN BUKTI IN VITRO SERTA IN VIVO - Elisa Issusilaningtyas; Septiana Indratmoko; Rianatul Chasanah; Tatang Tajudin; Rizki Azmi Nurmajid (Jurnal Buana Farma, 2026)
Diabetes mellitus is a chronic metabolic disease with an increasing global prevalence and remains a major cause of microvascular and macrovascular complications. Plant-derived antidiabetic agents have attracted considerable attention due to their therapeutic potential and relatively low adverse effects.Yakon (Smallanthus sonchifolius) leaves contain numerous bioactive compounds that may regulate glucose homeostasis through multiple molecular pathways. This study systematically reviewed the available scientific evidence regarding the antidiabetic activity of Smallanthus sonchifoliusleaves based on in vitro and in vivo studies. A Systematic Literature Review was conducted following PRISMA 2020 guidelines. Literature searches were performed in the Scopus database using the keywords "Smallanthus sonchifolius" OR "yacon leaves" AND antidiabetic OR diabetes mellitus for articles published between 2016 and 2025. Eligible studies included English-language original research articles available in full text investigating the antidiabetic effects of yacon leaves. Twenty-seven articles were identified, and fifteen studies met all inclusion criteria. The findings demonstrated that extracts, fractions, and infusions of yakon leaves consistently reduced blood glucose levels through antioxidant activity, enhanced insulin sensitivity, activation of the IRS-1/PI3K/Akt signaling pathway, inhibition of α-glucosidase and α-amylase enzymes, and modulation of DPP-IV activity. Major bioactive compounds responsible for these effects include polyphenols, flavonoids, chlorogenic acid, sesquiterpene lactones, and fructooligosaccharides. Although current evidence is predominantly preclinical, yakon leaves represent a promising phytotherapeutic candidate for diabetes management and warrant further clinical investigation.